Multilevel noncontiguous spinal fractures in adolescent idiopathic scoliosis: A report of three cases - Chris Yin Wei Chan; Kumar Shantanu Anand; Mun Keong Kwan (Indian Spine Journal, 2020)
This is a report of three cases of patients with Adolescent Idiopathic Scoliosis who presented with multilevel noncontiguous fractures of the spine. Interestingly, the apical vertebrae of the scoliotic curve were involved in all these three cases. The first patient had a fracture at apical T7 of the main thoracic curve and a fracture dislocation at apical L1 at the compensatory lumbar curve. In the second patient, the fractures occurred at the apex of a lumbar major curve and the compensatory main thoracic curve at L2 and T8, respectively. In the third patient, one of the four fractures occurred over the apex of thoracic curve at T8. Therefore, when a patient with idiopathic scoliosis presents following a high-energy accident, a higher index of suspicion should be maintained to diagnose multilevel fractures, especially over the apical vertebrae. Minimally Invasive Stabilization technique is useful in the stabilization of multilevel noncontiguous spinal fractures in these patients.